Practical wisdom for an ethical evaluation practice - Hurteau, Marthe, 1949-; Archibald, Thomas (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This book provides a contemporary and thought-provoking exploration of the concept of practical wisdom--what it is and how it can be incorporated into evaluation practice. It defines what practical wisdom is, explores its roots, where it stands today, what constitutes the "wise" evaluator, and how we can develop sound judgment in an unpredictable and chaotic time. It brings together evaluation thought leaders and practitioners to examine the concept of practical wisdom. The authors' enlightening essays are interwoven with reflective strands comprised of commentaries, examples, and new ideas added by Hurteau and her colleagues that offer a recursive and intricate pattern of reflection on the topic of practical wisdom. This is a rare book because it moves beyond evaluation methodology to explore how practical wisdom can help us develop new and better solutions for difficult evaluation situations. It will become a standard reference for practitioners, trainers. and teachers of evaluation because it considers the history, ethics, and competencies that underpin practical wisdom, and examines the ways that this untaught skill can be applied, to do, as House says, "the right thing in the special circumstances of performing the job"-- Provided by publisher.
Keywords: Educational evaluation -- Research.; Wisdom.; Education -- Evaluation & Assessment.; Education: examinations and assessment.; elektronické knihy; electronic books